2012
DOI: 10.4274/jcrpe.846
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Small For Gestational Age Newborns: A Review

Abstract: Several studies have shown that small for gestational age (SGA) babies have a different hormonal profile than those born with a birth weight appropriate for gestational age (AGA). Thyroid hormones play an important role in growth and neurocognitive development. Only few studies analyzed the concentrations of thyroid-stimulating hormone (TSH) and thyroxine (T4) during fetal and extrauterine life in SGA and AGA newborns, and the existing data on the possible alterations of these hormones in postnatal life are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Thyroid hormone is a hormone that has been implicated in mammalian cardiac myocyte terminal differentiation (17, 19 -21) that may play a role in different terminal differentiation in early T fetuses. Low thyroid hormone levels are associated with fetal growth restriction, and there are low circulating total and free thyroid hormones in growth-restricted fetuses (30,45), although there was an insufficient sample to measure thyroid hormone levels in this study. However, free thyroxine and triiodothyronine are not different in cord blood between male and female fetuses (31,48).…”
Section: Discussionmentioning
confidence: 88%
“…Thyroid hormone is a hormone that has been implicated in mammalian cardiac myocyte terminal differentiation (17, 19 -21) that may play a role in different terminal differentiation in early T fetuses. Low thyroid hormone levels are associated with fetal growth restriction, and there are low circulating total and free thyroid hormones in growth-restricted fetuses (30,45), although there was an insufficient sample to measure thyroid hormone levels in this study. However, free thyroxine and triiodothyronine are not different in cord blood between male and female fetuses (31,48).…”
Section: Discussionmentioning
confidence: 88%
“… 2 Although the 2 terms are different, SGA is widely considered to be a proxy for IUGR, and weights below 2 SD would capture the majority of fetuses with IUGR. 3 …”
Section: Introductionmentioning
confidence: 99%
“…However, while some studies have demonstrated that babies born to women with inadequate dietary iodine intake in the third trimester had lower birth weights than those born to women with adequate intake [36,37], most of them showed no evidence of an association between UIC and birth weight [38][39][40]. This mismatch is based on a great heterogeneity among studies due to a different degree of iodine deficiency (severe vs. moderate-to-mild deficiency); different timing (first trimester, half-gestation, at birth), and different methodology in the evaluation [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The term intrauterine growth restriction (IUGR) is used to describe a fetus that cannot reach its growth potential due to placental insufficiency, and is associated with poor perinatal outcomes [11]. Although the two terms are different, SGA remains the best clinical surrogate for IUGR, since it would capture the majority of fetuses with this condition [12].…”
Section: Introductionmentioning
confidence: 99%